The budget-making process - Institute for Development Policy Analysis and Advocay (Dhaka, Bangladesh); Proshikhsan Shikhsa Kaj (Organization : Bangladesh); Shamunnay (Organization : Bangladesh) (Dhaka : University Press, 2002)
Budget making process with a particular focus on the allocation for the poor.
Includes bibliographical references (pages [325]-330).
Keywords: Budget -- Bangladesh; Poor -- Bangladesh; Bangladesh -- Appropriations and expenditures